Analisis dan Implementasi Algoritma SHA-1 dan SHA-3 pada Sistem Autentikasi Garuda Training Cost - Firlhi Kurniawan; Ari Kusyanti; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Garuda Training Cost is a web application for calculating the training costs for pilots and flight attendants developed in Garuda Indonesia Training Center. This application use SHA-1 hash function algorithm to secure user password in database. However, the weakness and colisions have been found in this algorithm, therefore this algorithm less secure. Hence, in this research authors will replace the SHA-1 with the algorithm successor, SHA-3. This algorithm will be implemented in login process, password change process and adding users process. Both algorithm will be tested and analyzed to determine the performance of the algorithm. There are three types of tests performed. The first is brute-force testing, second is avalanche effect testing and the final test is processing time testing. From the brute-force test result, SHA-3 algorithm much better than SHA-1. From the 30 times testing for 10-character password, the SHA-1 generated hash need average 14 hours 53 minutes and 51 seconds to find the plaintext. While SHA-3 generated hash need average 4 days 13 hours 6 minutes and 6 seconds to find the plaintext. For the avalanche effect testing, SHA-1 algorithm get a percentage change of 100%, while SHA-3 get 95%. For the processing time testing, SHA-1 algorithm is better because of SHA-3 higher complexity. Although two of three test SHA-1 is better, does not mean SHA-3 is not better. Minimum avalanche effect percentage for an algorithm is 50%. And that processing time is still in milliseconds unit, so that user do not feel the impact directly. In conclusion, the three these tests show that the SHA-3 has a higher resistance than the algorithm SHA-1.